Noninvasive measurement of mucosal immunity in a free‐ranging baboon population. Issue 2 (13th January 2020) - Gesquiere, Laurence R.; Habig, Bobby; Hansen, Christina; Li, Amanda; Freid, Kimberly; Learn, Niki H.; Alberts, Susan C.; Graham, Andrea L.; Archie, Elizabeth A.
Abstract: Ecoimmunological patterns and processes remain understudied in wild primates, in part because of the lack of noninvasive methods to measure immunity. Secretory immunoglobulin A (sIgA) is the most abundant antibody present at mammalian mucosal surfaces and provides an important first line of defense against pathogens. Recent studies show that sIgA can be measured noninvasively in feces and is a good marker of mucosal immunity. Here we validated a commercial ELISA kit to measure fecal IgA in baboons, tested the robustness of its results to variation in collection and storage conditions, and developed a cost‐effective in‐house ELISA for baboon fecal IgA. Using data from the custom ELISA, we assessed the relationship between fecal IgA concentrations and gastrointestinal parasite burden, and tested how sex, age, and reproductive effort predict fecal IgA in wild baboons. We find that IgA concentrations can be measured in baboon feces using an in‐house ELISA and are highly correlated to the values obtained with a commercial kit. Fecal IgA concentrations are stable when extracts are stored for up to 22 months at −20°C. Fecal IgA concentrations were negatively correlated with parasite egg counts ( Trichuris trichiura ), but not parasite richness. Fecal IgA did not vary between the sexes, but for males, concentrations were higher in adults versus adolescents. Lactating females had significantly lower fecal IgA than pregnant females, but neither pregnant nor lactating female concentrations differed significantly from cycling females. Males who engaged in more mate‐guarding exhibited similar IgA concentrations to those who engaged in little mate‐guarding. These patterns may reflect the low energetic costs of mucosal immunity, or the complex dependence of IgA excretion on individual condition. Adding a noninvasive measure of mucosal immunity will promote a better understanding of how ecology modulates possible tradeoffs between the immune system and other energetically costly processes in the wild. Abstract : Research Highlights: An ELISA was developed and validated to measure Immunoglobulin A (IgA) in baboon feces. High parasite burden is associated with low fecal IgA. Adult males have higher fecal IgA than adolescent males. Reproductive effort affects fecal IgA concentrations in females but not in males.